The possible protective effects of vitamin E and selenium administration in oxidative stress caused by high doses of glucocorticoid administration in the brain of rats - Beytut, Ebru; Yilmaz, Seval; Aksakal, Mesut; Polat, Seher (Elsevier Gmbh, Urban & Fischer Verlag, 2018)
Acute exposure to high doses of glucocorticoids (GCs) may potentially increase the basal levels of reactive oxygen species (ROS) by altering the defence capacity against oxidative damage. Also, antioxidants may affect the oxidative breakdown of tissues. Therefore, the aim of this work was to determine the effects of dietary intake vitamin E and selenium (Se) on lipid peroxidat ion (LPO) as thiobarbituric acid reactive substances (TBARS) and on the antioxidative defence mechanisms in the brain of rats treated with high doses of prednisolone. Two hundred and fifty adult male Wistar rats were randomly divided into five groups. The rats were fed a normal diet, but groups 3, 4, and 5 received a daily supplement in their drinking water of 20 mg vitamin E, 0.3 mg Se, and a combination of vitamin E and Se, respectively, for 30 days. For 3 days subsequently, the control (group 1) was treated with a placebo, and the remaining 4 groups were injected intramuscularly with 100 mg/kg body weight (bw) prednisolone. After the last administration of prednisolone, 10 rats from each group were killed at 4, 8, 12, 24, and 48 h and the activities of enzymes selenium-glutathione peroxidase (Se-GSH-Px) and catalase (CAT), and the levels of reduced glutathione (reduced GSH) and TSARS in their brains were measured. Se-GSH-Px and CAT enzyme activities, and reduced GSH levels in the prednisolone treatment group (group 2) began to decrease gradually at 4 h (p < 0.01, p < 0.05, respectively), falling respectively to 60, 50, and 40% of the control levels by 24 h (p < 0.001, p < 0.01), and recovering to the control levels at 48 h. In contrast, prednisolone administration caused an increase in the brain TBARS, reaching up to six times the level of the control at 24 h (p < 0.001). However, supplementation with vitamin E and Se had a preventive effect on the elevation of the brain TBARS and improved the diminished activities of antioxidative enzymes and the levels of reduced GSH. Therefore, the present study attempts to determine the sequence of cellular membrane damage in the brain of the rats after high doses GC administration and the possible roles in vivo of vitamin E and Se, and their combination.
Keywords: Mega dose of glucocorticoids; Vitamin E; Selenium; Brain; Oxidative stress